KONSTRUKSI MAKNA SENI TEATER DI KALANGAN ANGGOTA SANGGAR TEATER DI KOTA PEKANBARU - Intan Fakhriah Elfafriani; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Practicing theater arts is not easy, moreover when someone has decided tobecome an actor, there are some conditions to fulfill and basic trainings toendure. The hardships in the world of performing arts has made some members oftheater group became subjects of “natural selection” which has made them leftthe group and the world of performing arts, especially to them who intended tojust trying or joining only because their firends did so. Although, there are stillmany members stay and has decided to keep learning about theater arts. Thepurpose of this research is to discover motives, meanings of theater arts, andcommunication experiences which happened to the members of theater arts groupin Pekanbaru city.The research method used in this study is qualitative research method withphenomenology approach. Informants of this research are 8 members of 3 theaterstudios in Pekanbaru City whom got selected using purposive sampling technique.The data collection techniques are interview, observation and documentation.While the data analysis techniques including data reduction, data serving, generalconclusion and verification.The result of this research shows that the motives of theater studiomembers in Pekanbaru in joining theater arts consist of because-motives whichare curiosity, interests, invitation, pleasure and distaste. While the in-order-tomotivesconsist of existence, seeking for satisfaction, become useful to society, selfdevelopment and talent development. Meanings of theater arts constructed bytheater group members consist of theater arts as learning media, a room toexpress, and sel improvement. Pleasant experiences which has happened to thetheater group members at the time they learn about theater arts are kinship,harmony, togetherness, success in performing the show, gained the trust to directa performance, and achieving the awards. While the unpleasant experiences aremisbehavior of some members, conflicts among the internal group members,unable to read the audiences, exercising too hard, and being unappreciated.Keywords : Construction of Meaning, Phenomenology, Motives, Meanings,Communication Experience, Theater Arts